Student Teachers experiences of an Online Team-Based Learning Strategy Applied in an ODeL Course - van Wyk, Micheal M (Research in Social Sciences and Technology, 2025)
The purpose of the online course, Teaching Methodology Economics in the Further Education and Training Phase, is to expose student teachers to the online team-based learning (TBL) strategy as a collaborative teaching and learning approach that allows them to follow an organised procedure. To increase student engagement, accountability and collaboration in the course, an open distance e-learning (ODeL) environment can benefit from the active, structured small group learning that team-based learning offers. An ODeL course at a College of Education employed TBL as an example of a flipped instructional design. The experiences of the Teaching Methodology Economics student teachers participating in an online TBL strategy served as the basis for the single case study reported, which employed a exploratory qualitative approach. The study purposively selected only five participants (n = 5) for the interviews. Transcripts were produced by the computerised NVivo 14 software and thematic analysis was generated themes reflecting the participating student teachers’ experiences of the TBL strategy. The findings revealed that participants developed professional attributes, were motivated to reflect on their strengths and weaknesses as members of teams, and experienced the value of working and collaborating in groups. Further research on the use of evidence-based practice will ensure better outcomes for TBL in flipped learning contexts.